A Simple and Easy Way to Enhance Sensitivity of Sn(IV) on Bismuth Film Electrodes with the Use of a Mediator - Tyszczuk-Rotko, Katarzyna; Metelka, Radovan; Vytřas, Karel; Barczak, Mariusz; Sadok, Ilona; Miroslaw, Barbara (My University, 2016)
For the first time an in situ-plated bismuth film electrode prepared with the use of a reversibly deposited mediator (Zn) was applied to anodic stripping voltammetry of the metal ions. This simple and easy way of the electrode surface modification by metal films was suggested to increase the voltammetric signal of Sn(IV) and, consequently, to improve the sensitivity and tin detection limit. The structural and chemical information about the bismuth films plated with and without the use of the mediator were derived from AFM and XPS data analysis.
Jednoduchý a nenáročný způsob zvýšení citlivosti stanovení Sn(IV) na bismutových filmových elektrodách s použitím mediátoru
Keywords: Electrochemistry; Voltammetry; Sensors; Surface; Tin determination; Elektrochemie; voltametrie; senzory; povrch; stanovení cínu